Improving lithium–sulfur battery performance via a carbon-coating layer derived from the hydrothermal carbonization of glucose. Issue 63 (10th July 2015) - Zhang, Songtao; Li, Nianwu; Lu, Hongling; Zheng, Jiafei; Zang, Rui; Cao, Jieming
<x xml:space="preserve">Abstract</x> After wrapping AC–S with a carbon-coating layer, the obtained composite can effectively confine polysulfides.